निम्नलिखित को सिद्ध कीजिए
$\sin ^{2} 6 x-\sin ^{2} 4 x=\sin 2 x \sin 10 x$
It is known that
$\sin A+\sin B=2 \sin \left(\frac{A+B}{2}\right) \cos \left(\frac{A-B}{2}\right), \sin A-\sin B=2 \cos \left(\frac{A+B}{2}\right) \sin \left(\frac{A-B}{2}\right)$
$\therefore$ $L.H.S.$ $=\sin ^{2} 6 x-\sin ^{2} 4 x$
$=(\sin 6 x+\sin 4 x)(\sin 6 x-\sin 4 x)$
$=\left[2 \sin \left(\frac{6 x+4 x}{2}\right) \cos \left(\frac{6 x-4 x}{2}\right)\right]\left[2 \cos \left(\frac{6 x+4 x}{2}\right) \cdot \sin \left(\frac{6 x-4 x}{2}\right)\right]$
$=(2 \sin 5 x \cos x)(2 \cos 5 x \sin x)=(2 \sin 5 x \cos 5 x)(2 \sin x \cos x)$
$=\sin 10 x \sin 2 x$
$= R . H.S$
$\sin \frac{\pi }{{14}}\sin \frac{{3\pi }}{{14}}\sin \frac{{5\pi }}{{14}}\sin \frac{{7\pi }}{{14}}\sin \frac{{9\pi }}{{14}}\sin \frac{{11\pi }}{{14}}\sin \frac{{13\pi }}{{14}}$ का मान होगा
यदि $\sin \theta + \cos \theta = x,$ तब ${\sin ^6}\theta + {\cos ^6}\theta = \frac{1}{4}[4 - 3{({x^2} - 1)^2}]$ होगा
यदि $\sin \theta + \sin 2\theta + \sin 3\theta = \sin \alpha $ तथा $\cos \theta + \cos 2\theta + \cos 3\theta = \cos \alpha $, तब $\theta$ का मान होगा
यदि $\tan A = \frac{{1 - \cos B}}{{\sin B}},$ तो $\tan 2A$ को $\tan B$ के पदों में निकालिए और दिखलाइए कि
यदि ${\cos ^6}\alpha + {\sin ^6}\alpha + K\,{\sin ^2}2\alpha = 1,$ हो तो $K $ का मान होगा